Mitigating Co-channel interference using transmitter pre-processing for double space-time transmit diversity aided IDMA system. (May 2017) - Kalaiarasan, R.; Vishvaksenan, K.S.
Highlights: We investigate the error-rate performance ofturbo coded DSTTD-IDMA system using transmitter pre-processing for DL transmission. Error-rate Performance of turbo coded DSTTD-IDMA system is compared with uncoded system and demonstrated that coded system achieves better results in terms of achievable error-rate performance. Our considered MUTP aided coded DSTTD-IDMA system achieves higher data rate with compact size of Mobile station. Abstract: A double space-time transmit-diversity (DSTTD) architecture achieves higher throughput by employing four transmit antennas and four receive antennas. In this article, we compute Error-Rate (ER) performance of DSTTD-Interleave-division multiple-access (IDMA) system using Multi-user transmitter pre-processing (MUTP) for standard channel models. We realize MUTP using SVD technique to mitigate Co-channel interference (CCI) effects apart from Multi-user Interference (MUI), which are considered to be major channel impairments. The MUTP exploits the signal space of the entire active user's channel state information (CSI). We estimate CSI and quantize using vector quantization at each mobile unit and formulate TP by recovering at base station. Our simulation result reveals that considered system with MUTP technique achieves better ER with less SNR while offering high data rate for downlink transmission. Further, we observe that the ER performance of our considered system depends on code book size of vector quantized parameters. Graphical abstract: